A New Possibility of Dynamical Study on Solid State Ionic Materials by Inelastic Neutron Scattering - M. Nakamura; K. Nakajima; Y. Inamura; S. Ohira Kawamura; T. Kikuchi; T. Otomo; M. Arai (Atom Indonesia, 2010)
A new technique of inelastic neutron scattering measurement utilizing the multiple incident energies is applied to the dynamical study of vitreous silica. A wide variety of extracted information from a series of two-dimensional maps of dynamical structure factor with multiple different incident energies are greatly valuable. The applicability and its expected contribution of new experimental technique into the further progress of scientific activities in solid state ionic materials are discussed.Received: 30 September 2010; Revised: 25 October 2010; Accepted: 26 October 2010